A fotografia multiespectral na arquitectura: Uma abordagem experimental como ferramenta de análise e trabalho - Ruben Alves Venceslau (2017)
Due to the current economic conditions, building rehabilitation is a trending subject, therefore, it becomes imperative to use methods and techniques that facilitate the process of knowing what to rehabilitate. This study proposes the application of photography as a tool of analysis and non-invasive diagnosis of the built heritage. Was developed through a process of photographic records, using photographic and thermographic cameras, capturing not only the visible portion as well the invisible part of the electromagnetic spectrum, such as infrared and ultraviolet radiation. A sample with 13 study cases was selected from three main parameters: architectural value, ease access and possible areas of interest, resulting an example of practical application of the analysis system. The techniques of diagnostic allow the evaluation of anomalous conditions in building, developing a non-invasive evaluation methodology and, consequently, expanding the range of non-invasive analysis techniques and hidden from the human eye.